A design procedure for a supervisory control structure in plantwide control (2014)
Abstract: This work presents a methodology for designing a supervisory control structure in Plant-wide Control (PWC). First, available PWC structures are discussed focusing on their drawbacks originated from the scarce flexibility and simplicity when implementing them in industrial environments. Additionally, the available control strategies involve decoupling of the process, losing all interactions information and therefore requiring more complex models inside the control structure to account for interactions among units. To overcome this, a hierarchical approach to PWC is proposed, introducing a two–layer control structure where dynamics on the regulatory layer are classified by hierarchical association considering that process dynamics and their set–points are optimized on the supervisory layer to achieve collaboration among Proportional–Integral–Derivative (PID) controllers in the regulatory layer. A dynamics hierarchy is established by means of the process Hankel matrix that quantifies the effect of all input variables over each state variable of the plant. Finally, the proposed methodology is applied to a Reactor–Separator–Recycle system for propylene glycol production, where a better process performance is reached using the hierarchical approach in comparison with the decentralized proposal.